The Fine Art of Writing Posthumous Papers: On the Dubious Role of the Romantic Fragment in the First Part of Either/Or - Bøggild, Jacob (KIERKEGAARDIANA, 1998)
The Fine Art of Writing Posthumous Papers: On the Dubious Role of the Romantic Fragment in the First Part of Either/Or